Leadership Style, Work Motivation, and Work Discipline on Teacher Performance at Miftahul Jannah Elementary School in Sragen Regency - Widita Cahya Putri; Eny Kustiyah; Sitti Mukarromah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The influence of leadership style, work motivation, and work discipline on teacher performance at SDIT Miftahul Jannah. This study uses a quantitative approach with a causal associative research type. In this study, the influence of leadership style, work motivation, and work discipline on teacher performance at SDIT Miftahul Jannah in Sragen Regency will be analyzed. The data collected are in the form of numbers from the questionnaire results which are processed and analyzed using statistical methods. This research was conducted at SDIT Miftahul Jannah, Sragen Regency. The research implementation time was carried out for two months, namely in November - December 2025. The population in this study was 40 teachers who worked at SDIT Miftahul Jannah, Sragen Regency, consisting of class teachers and subject teachers, and the sample used was 40 respondents. The sampling technique used in this study was saturated sampling (census). The variables in this study consisted of the Free Variable (Independent), namely Leadership Style, Work Motivation, Work Discipline. Then the Dependent Variable variable was Teacher Performance. To determine the influence of leadership style, work motivation and work discipline on teacher performance at SDIT Miftahul Jannah in Sragen Regency, multiple regression analysis was used. Based on the results of research and discussion regarding the influence of leadership style, work motivation and work discipline on teacher performance at SDIT Miftahul Jannah, the following conclusions can be drawn: Leadership style, work motivation and discipline have a positive and significant effect on teacher performance.